European HPC Landscape - Berberich, Florian; Liebmann, Janina; Teodor, Veronica; Nominé, Jean-Philippe; Pineda, Oriol; Segers, Philippe (COMPUTING AND INFORMATICS, 2021)
This paper provides an overview on the European HPC landscape supported by a survey, designed by the PRACE-5IP project, accessing more than 50 of the most influential stakeholders of HPC in Europe. It focuses at Tier-0 systems on the European level providing high-end computing and data analysis resources. The different actors are presented and their provided services are analyzed in order to identify overlaps and gaps, complementarity and opportunities for collaborations. A new pan-European HPC portal is proposed in order to get all information on one place and facilitate access to the portfolio of services offered by the European HPC communities.